2021
DOI: 10.1007/s12032-021-01579-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electroporation on anticancer activity of 5-FU and newly synthesized zinc(II) complex in chemotherapy-resistance human brain tumor cells

Abstract: Zn(II) complex of Schiff base derived from the condensation of 4-aminopyrimidine-2(1H)-one with salicylaldehyde was prepared and characterized by various physico-chemical and spectral methods for structure determination. The cytotoxic activity of the Zn(II) complex was investigated in comparison with 5-uorouracil (5-FU) against two different human brain tumor cell lines (T98G and U118), while primer human dermal broblast cells (HDF) was used as control for biocompatibility. Then, the effectiveness of electropo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
1
0
1
Order By: Relevance
“…A study by Yang et al (2022) stated that the Selenium in combination with doxorubicin has high attenuation of cancer cells. Similarly, the combination of Zinc and 5-FU complexes showed anti-cancer activity against brain tumor cells and breast tumor cells ( Hu et al, 2012 ; Alkış et al, 2021 ). As mentioned in the study of Saranya et al (2022) , It has been found that the combination of apigenin with Se NPs significantly increases MDA (malondialdehyde) production in cancer cells, suggesting it is a potential therapeutic approach in the fight against breast cancer.…”
Section: Resultsmentioning
confidence: 98%
“…A study by Yang et al (2022) stated that the Selenium in combination with doxorubicin has high attenuation of cancer cells. Similarly, the combination of Zinc and 5-FU complexes showed anti-cancer activity against brain tumor cells and breast tumor cells ( Hu et al, 2012 ; Alkış et al, 2021 ). As mentioned in the study of Saranya et al (2022) , It has been found that the combination of apigenin with Se NPs significantly increases MDA (malondialdehyde) production in cancer cells, suggesting it is a potential therapeutic approach in the fight against breast cancer.…”
Section: Resultsmentioning
confidence: 98%
“…ECT'de uygulanacak darbe parametreleri hücre içine antikanser ajan geçişini kolaylaştırırken, minimum düzeyde hücre ölümüne neden olmalıdır. Daha önce yapılan in vitro ECT çalışmalarında tek başına uygulanan elektroporasyonun, değişik oranlarda hücre ölümüne neden olabildiği bildirilmiştir [8,26,27,28,29]. Uygulanan elektrik darbelerinin tipi, sayısı, süresi, frekansı ve genliği gibi parametreler hücre geçirgenliğini, ölümünü ve altyapısını değiştirebilmektedir [30].…”
Section: Bulgular Ve Tartişmaunclassified